Are MSMEs Able to Prepare Financial Statements Following SAK EMKM? - Zaenal Wafa; Florentina Rusmawati; Rochmad Bayu Utomo; Martinus Budiantara; Azfa Mutiara Ahmad Pabulo (Jurnal Ekonomi dan Bisnis Digital, 2023)
Micro, small, and Medium Enterprises (MSMEs) are the most popular businesses by the Indonesian people and have large role, absorption of labor for the national economy. MSMEs grow and develop in areas rich with high natural and human resources rate but only 19.6% of MSMEs have implemented SAK EMKM in their financial record. The purpose of this study in Kalurahan Tridadi is to find understanding accounting, utilization of information technology, and socialization influence financial statements in MSMEs. This research uses quantitative methods with an associative approach. The study found that financial statements of MSME actors are prepared well, with socialization provided to help them understand and implement financial report preparation activities.